Highly Sensitive Ultrathin Flexible Thermoplastic Polyurethane/Carbon Black Fibrous Film Strain Sensor with Adjustable Scaffold Networks - Wang, Xin; Liu, Xianhu; Schubert, Dirk W. (Nano-Micro Letters, 2021)
In recently years, high-performance wearable strain sensors have attracted great attention in academic and industrial. Herein, a conductive polymer composite of electrospun thermoplastic polyurethane (TPU) fibrous film matrix-embedded carbon black (CB) particles with adjustable scaffold network was fabricated for high-sensitive strain sensor. This work indicated the influence of stereoscopic scaffold network structure built under various rotating speeds of collection device in electrospinning process on the electrical response of TPU/CB strain sensor. This structure makes the sensor exhibit combined characters of high sensitivity under stretching strain (gauge factor of 8962.7 at 155% strain), fast response time (60 ms), outstanding stability and durability (> 10,000 cycles) and a widely workable stretching range (0–160%). This high-performance, wearable, flexible strain sensor has a broad vision of application such as intelligent terminals, electrical skins, voice measurement and human motion monitoring. Moreover, a theoretical approach was used to analyze mechanical property and a model based on tunneling theory was modified to describe the relative change of resistance upon the applied strain. Meanwhile, two equations based from this model were first proposed and offered an effective but simple approach to analyze the change of number of conductive paths and distance of adjacent conductive particles. Highlights: 1 The sensors displayed high sensitivity (8962.7), fast response time (60 ms), outstanding stability and durability (> 10,000 cycles) and widely workable stretching range (0–160%). 2 A theoretical approach was used to analyze mechanical property, and a model based on tunneling theory was modified to describe the relative change of resistance. 3 Two equations were proposed and offered an effective but simple approach to analyze the change of number of conductive paths and distance of adjacent conductive particles.